MCourier System - Mualuko Ndanu Purity; Mualuko Ndanu Purity (Meru : Mualuko Ndanu Purity, 2013)
MCourier is a proposed mobile application that will help expand the working boundaries of DHL courier services provider.DHL is a company that deals with delivery of goods and parcels on an international level.
A project submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Computer Science